Pyrosequencing Reveals a Core Community of Anodic Bacterial Biofilms in Bioelectrochemical Systems from China - Xiao, Yong; Zheng, Yue; Wu, Song; Zhang, En-Hua; Chen, Zheng; Liang, Peng; Huang, Xia; Yang, Zhao-Hui; Ng, I-Son; Chen, Bor-Yann; Zhao, Feng (Frontiers in Microbiology, 2015)
Bioelectrochemical systems (BESs) are promising technologies for energy and product recovery coupled with wastewater treatment, and the core microbial community in electrochemically active biofilm in BESs remains controversy. In the present study, 7 anodic communities from 6 bioelectrochemical systems in 4 labs in southeast, north and south-central of China are explored by 454 pyrosequencing. A total of 251,225 effective sequences are obtained for 7 electrochemically active biofilm samples at 3% cutoff level. While Alpha-, Beta- and Gamma-proteobacteria are the most abundant classes (averaging 16.0-17.7%), Bacteroidia and Clostridia are the two sub-dominant and commonly shared classes. Six commonly shared genera i.e. Azospira, Azospirillum, Acinetobacter, Bacteroides, Geobacter, Pseudomonas and Rhodopseudomonas dominate the electrochemically active communities and are defined as core genera. A total of 25 OTUs with average relative abundance >0.5% were selected and designated as core OTUs, and some species relating to these OTUs have been reported electrochemically active. Furthermore, cyclic voltammetry and chronoamperometry tests show that two strains from Acinetobacter guillouiae and Stappia indica, bacteria relate to two core OTUs, are electrochemically active. Using randomly selected bioelectrochemical systems, the study presented extremely diverse bacterial communities in anodic biofilms, though, we still can suggest some potential microbes for investigating the electrochemical mechanisms in bioelectrochemical systems.